INFLUENCE OF DIGITAL MARKETING AND SALES PROMOTION TOWARDS PRODUCT PURCHASE DECISIONS AT IVY CARISSA SIMO FASHION STORE - Gina Sila Nuryana; Isfadhilah; Anis Fitriyasari (Pedagogic Research-Applied Literacy Journal, 2024)
The purpose of this study is to examine the role of digital marketing and discount towards purchasing decisions at Ivy Carissa fashion store. The primary sample data was taken from Ivy Carissa customers. The questionnaire contains 13 items of questions. The data were analyzed using descriptive quantitative method and using multiple linear regression. The results showed that digital marketing effect significantly on purchasing decisions. The same goes to discount that effect significantly on purchasing decisions. Simultaneously variables of digital marketing and discount effects on purchasing decisions.